2014
DOI: 10.1021/jm401893j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structure–Activity Relationships, and Biological Studies of Chromenochalcones as Potential Antileishmanial Agents

Abstract: Antileishmanial activities of a library of synthetic chalcone analogues have been examined. Among them, five compounds (11, 14, 16, 17, 22, and 24) exhibited better activity than the marketed drug miltefosine in in vitro studies against the intracellular amastigotes form of Leishmania donovani. Three promising compounds, 16, 17, and 22, were tested in a L. donovani/hamster model. Oral administration of chalcone 16, at a concentration of 100 mg/kg of body weight per day for 5 consecutive days, resulted in >84% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 56 publications
(96 reference statements)
0
12
0
Order By: Relevance
“…These observations may indicate parasite death caused by apoptosis. Shivahare et al (2014) [ 35 ] showed that a chromenochalcone exhibited leishmanicidal effects against Leishmania donovani by causing loss in membrane potential and phosphatidylserine exposure, thus exerting cell death via apoptosis in treated promastigotes.…”
Section: Discussionmentioning
confidence: 99%
“…These observations may indicate parasite death caused by apoptosis. Shivahare et al (2014) [ 35 ] showed that a chromenochalcone exhibited leishmanicidal effects against Leishmania donovani by causing loss in membrane potential and phosphatidylserine exposure, thus exerting cell death via apoptosis in treated promastigotes.…”
Section: Discussionmentioning
confidence: 99%
“…The chalcones, that have this structural feature, are among the important compounds that we frequently encounter in the literature in terms of both their useful synthetic properties and biological activity they exhibit . They have a broad spectrum of biological activity such as antimicrobial, antifungal, anticancer, anti‐inflammatory, analgesic, antioxidant, antileishmanial and antimalarial activities. In addition, many heterocyclic and polyfunctional compounds such as pyrazole, pyrimidine, pyridine, pyridone, quinoline and isoxazole derivatives can be synthesized easily starting from chalcones.…”
Section: Introductionmentioning
confidence: 99%
“…Chalcones or 1,3‐diaryl‐2‐propen‐1‐ones (Figure ) belonging to the flavonoid family are natural products with wide spread distribution in fruits, vegetables, spices and tea. Recently, the compounds with chalcone (1,3‐diaryl‐2‐propen‐1‐one) backbone have been reported to exhibit diverse biological properties, including antimalarial, antiviral, antibacterial, antituberculosis, antifungal, anticancer, antileishmaninal, antigiardial and antiinflammatory . A number of chalcone derivatives have also been found to inhibit several important enzymes in cellular systems, including protein tyrosine kinase, malarial aspartic protease (PM II) and malarial cysteine protease (FP‐1) .…”
Section: Introductionmentioning
confidence: 99%